Environmental & architectural phenomenology. Vol. 17, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2006)
Vol. 17, No. 1, Winter 2006 (includes “items of interest,” “citations received,” and essays by Dylan Trigg & Chris Aanstoos).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals